TINJAUAN YURIDIS TENTANG PEMBATALAN EKSEKUSI JAMINAN FIDUSIA OLEH BPSK - Richard Richard Richard (jurnal.unprimdn.ac.id, 2018)
Fiduciary guarantee is a guarantee against movable objects or other objects not charged by mortgage. The current provision of fiduciary guarantees is generally given to movable objects, especially motorized vehicles. Fiduciary guarantees themselves occur based on financing agreements between debtors and creditors with legal relationships based on fiduciary guarantee laws and consumer protection laws. Fiduciary creditor is a privileged creditor based on fiduciary guarantee law so that when the debtor fails to promise the creditor can immediately execute the debtor's guarantee without waiting for a court decision. This is based on the ordinance on the fiduciary deed which is equated with a court ruling like what is stipulated in the fiduciary guarantee law. But if you look at the relationship between debtors and fiduciary creditors based on consumer protection laws, the debtor is given the position as a consumer and creditor as a business actor. So when consumers feel aggrieved they can take legal remedies to BPSK as a consumer dispute settlement institution as mandated by the Consumer Protection Act. However, it is interesting to see when a debtor or consumer is considered to be in default by a creditor or business actor. While the debtor feels aggrieved and takes legal action to BPSK and when BPSK turns out to cancel the execution of the fiduciary guarantee there will be a legal conflict between the BPSK decision and the fiduciary guarantee law that privileges the creditor of fiduciary guarantees